APHORISMS AND TEXTS OF THE "MOTHERLAND" CONCEPT EXPRESSION IN DIFFERENT LANGUAGES WITH HELP - Mavlanova Dildora Saidnazarovna (Web of Journals Publishing, 2023)
This article aims to study the expression of the concept of "Motherland" different languages by means of aphorisms and texts. In the study of approaches to the homeland, special attention is paid to the importance of a set of phrases found at a certain time and helping to understand the truth about this concept by philosophers, sages, famous historical figures.
Keywords: Aphorisms, phrases, concept, Motherland, hadith, immigrant, faith.